Screening, Characterization, and Cultivation of Cellulase-Producing Bacteria as Probiotic Candidates for Poultry - Anwar, Khairil; Sukarne; Unsunnidhal, Lalu; Fitriyan Fadjar Suryadi, Muh. Aidil; Junia Ayu Ninggrum, ⁠Vidia; Aryadin Putra, Ryan; Al Gifari, Zaid; Septian, I Gede Nano; Aminurrahman; Ali, Muhamad (Universitas Bengkulu, 2025)
Probiotics play an essential role in regulating gut microbiota and increasing feed digestibility in poultry. This study aimed to screen and characterize cellulase-producing bacteria as poultry probiotic candidates. Among the five isolates tested, isolates I5 and BP had cellulase activity, as indicated by clear zones surrounding the colonies on carboxymethyl cellulose (CMC) agar plates. Isolate I5 was more tolerant to low pH and 0.3% bile salts than isolate BP, indicating probiotic potential. Isolate I5 was selected for cultivating in tempeh wastewater-molasses medium (TM) and LB medium at 37 °C with shaking at 120 rpm. The results demonstrated that bacterial growth in TM medium was significantly lower (p < 0.001) than in LB medium. Importantly, bacterial growth in TM medium reached an optical density (OD₆₀₀) of 0.415 after 6 hours of incubation, indicating its adaptability to tempeh wastewater-molasses medium. These findings suggest that the TM medium promotes bacterial growth and proliferation, supports probiotic and enzyme production for use in poultry feed supplementation, and reduces cultivation costs. Therefore, the use of agro-industrial waste provides a cost-effective alternative for cultivating cellulase-producing probiotics, thereby contributing to value-added waste management, sustainable poultry production, and circular bio-economy practices.